EFEKTIFITAS PENGGUNAAN RESEP ELEKTRONIK TERHADAP MANAJEMEN KEUANGAN RUMAH SAKIT - Ellyana, Ellyana; Nining Handayani; Ignatius Wiseto P Agung (Bajang Institute, 2025)
Hospital financial management is influenced by the effectiveness of information systems, one of which is the prescription management process. Manual systems often result in cost inefficiencies, delays in record-keeping, and inaccuracies in drug transaction data. The implementation of an electronic prescription (e- prescription) system is expected to improve efficiency and transparency in hospital financial management. The research question in this study is how effective is the implementation of e-prescriptions in supporting hospital financial management. his study employs a qualitative. Data were collected through in-depth interviews with seven informants at Sentra Medika Cisalak Hospital. Data analysis was conducted using SWOT analysis. The results show that the implementation of the e- prescription system has had a positive impact on hospital financial management. The system accelerates the recording process of drug transactions, reduces administrative errors, and helps the hospital monitor expenditures more accurately and in real time. E-prescriptions also support rational drug use and strengthen procurement systems based on actual needs. However, some initial implementation challenges were identified, including human resource adaptation, initial investment costs, and limited automatic reporting features. The conclusions of this study are: 1. E-prescription implementation is highly effective in drug logistics, distribution, and reporting transparency. 2. The main challenges include the need for initial investment, human resources, system integration, and technical disruptions. 3. E- prescriptions improve drug cost management and reduce financial recording errors.